Isolation-Aware Timing Analysis and Design Space Exploration for Predictable and Composable Many-Core Systems - Pourmohseni, Behnaz; Smirnov, Fedor; Wildermann, Stefan; Teich, Jürgen (Proceedings of the 31th Euromicro Conference on Real-Time Systems (ECRTS), 2019)
Composable many-core systems enable the independent development and analysis of applications which will be executed on a shared platform where the mix of concurrently executed applications may change dynamically at run time. For each individual application, an off-line DSE is performed to compute several mapping alternatives on the platform, offering Pareto-optimal trade-offs in terms of real-time guarantees, resource usage, etc. At run time, one mapping is then chosen to launch the application on demand. In this context, to enable an independent analysis of each individual application at design time, so-called inter-application isolation schemes are applied which specify temporal/spatial isolation policies between applications. State-of-the-art composable many-core systems are developed based on a fixed isolation scheme that is exclusively applied to every resource in every mapping of every application and use a timing analysis tailored to that isolation scheme to derive timing guarantees for each mapping. A fixed isolation scheme, however, heavily restricts the explored space of solutions and can, therefore, lead to suboptimality. Lifting this restriction necessitates a timing analysis that is applicable to mappings with an arbitrary mix of isolation schemes on different resources. To address this issue, in this paper, we (a) present an isolation-aware timing analysis that - unlike existing analyses - can handle multiple isolation schemes in combination within one mapping and delivers safe yet tight timing bounds by identifying and excluding interference scenarios that can never happen under the given combination of isolation schemes. Based on the timing analysis, we (b) present a DSE which explores the choices of isolation scheme per resource within each mapping and uses the proposed timing analysis for timing verification. Experimental results demonstrate that, for a variety of real-time applications and many-core platforms, the proposed approach achieves an improvement of up to 67% in the quality of delivered mappings compared to approaches based on a fixed isolation scheme.
Keywords: Many-core systems; timing analysis; design space exploration (DSE); isolation scheme; predictability; composability